2018
DOI: 10.29115/sp-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Within-Household Selection and Dual-Frame Telephone Surveys: A Comparative Experiment of Eleven Different Selection Methods

Abstract: Numerous within-household selection methods have been tested in general population surveys since the advent of telephone interviewing. However, very few selection studies, if any, have been conducted with a dual frame (landline and cell phone) sample. Landline and cell phone frames are known to represent demographically different groups of respondents, and selection methods that may result in more representative demographics in a landline frame may actually skew the results when combined with the cell phone fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Non-probabilistic selection techniques, for example, TCB and arbitrary convenience methods are generally used to increase cooperation with the respondent and diminish cost. Marlar et al (2018) found the highest response rates with non-probabilistic within-household methods while the lowest accuracy rates were observed for quasi-probability birthday methods. Although they do not follow a complete random cycle, such methods attempted to approximate gender and age distributions and give a premise for modified versions of choice strategies (Gaziano, 2005).…”
Section: Literature Reviewmentioning
confidence: 86%
See 2 more Smart Citations
“…Non-probabilistic selection techniques, for example, TCB and arbitrary convenience methods are generally used to increase cooperation with the respondent and diminish cost. Marlar et al (2018) found the highest response rates with non-probabilistic within-household methods while the lowest accuracy rates were observed for quasi-probability birthday methods. Although they do not follow a complete random cycle, such methods attempted to approximate gender and age distributions and give a premise for modified versions of choice strategies (Gaziano, 2005).…”
Section: Literature Reviewmentioning
confidence: 86%
“…There are plenty of studies that examine within-household selection procedures as well as their strengths and weaknesses, especially for the US survey settings. In other words, there exists literature on within-household selection procedures and their impact on statistics in the US surveys (Alves et al, 2014;Lavrakas, 1993;Lavrakas, 2008;Lavrakas and Bauman, 1993;Lavrakas et al, 2000;Marlar et al, 2018;Marken, 2018;Smyth et al, 2019). In later and earlier, a large portion of the examinations focuses on the Kish technique which follows the probabilistic selection procedure (Kish, 1949).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation